2012
DOI: 10.1111/j.1360-0443.2012.03887.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of ethical issues in using wastewater analysis to monitor illicit drug use

Abstract: Aims  To discuss ethical issues that may arise in using WWA to monitor illicit drug use in the general population and in entertainment precincts, prisons, schools and work‐places. Method  Review current applications of WWA and identify ethical and social issues that may be raised with current and projected future uses of this method. Results  Wastewater analysis (WWA) of drug residues is a promising method of monitoring illicit drug use that may overcome some limitations of other monitoring methods. When used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 34 publications
1
59
0
1
Order By: Relevance
“…disadvantaged suburb) [37]. In view of the negligible risk of (in)direct harm to residents, no ethical issues are expected for WWA studies in large, general populations (ballpark ≥10 000 people) if findings do not relate to a specific group (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…disadvantaged suburb) [37]. In view of the negligible risk of (in)direct harm to residents, no ethical issues are expected for WWA studies in large, general populations (ballpark ≥10 000 people) if findings do not relate to a specific group (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the negligible risk of (in)direct harm to residents, no ethical issues are expected for WWA studies in large, general populations (ballpark ≥10 000 people) if findings do not relate to a specific group (e.g. disadvantaged suburb) [37]. In the future, WWA may be particularly useful to determine differences between rural and metropolitan areas and to calculate representative country-wide averages.…”
Section: Discussionmentioning
confidence: 99%
“…The selected WTP 5 has a capacity of 94,000 population-equivalents corrected to 70,000 inhabitants (inh) considering the number of inhabitants on the catchment. Because IDs are not innocuous pollutants from a political and epidemiological point of view, the exact emplacement of the WTP investigated in this study is not disclosed, in accordance with ethical guidelines (Hall et al, 2012;Prichard et al, 2014)…”
Section: Sample Collection and General Settingmentioning
confidence: 99%
“…The method provides an objective and non-intrusive way of measuring drug consumption in the population contributing to a sewer catchment. The method also protects individual anonymity because samples are collected from pooled and intermingled wastewater, avoiding potential ethical issues arising from identifying urine samples of individual drug users [9]. It has been demonstrated that data from wastewater analysis can be an effective complement to traditional epidemiological methods for studying illicit drug use (e.g.…”
Section: Introductionmentioning
confidence: 99%